Implikasi Pengembalian Keuangan Negara Terhadap Putusan Hakim dalam Perkara Tindak Pidana Korupsi Dana Bantuan Program Nasional Pembangunan Masyarakat Mandiri Pedesaan di Provinsi Lampung - Zainudin Hasan (Universitas Bandar Lampung (UBL), 2018)
National Community Empowerment Program Mandiri (PNPM) Rural is one mechanism of community empowerment programs that are used through PNPM Mandiri women's savings and loan (SPP) management.Supervision of the PNPM Mandiri Rural SPP management systems and mechanisms is still very weak in relation to the mechanism of management, supervision and accountability of fund disbursement.The problem of this research is how is criminal responsibility for the perpetrators of corruption of PNPM assistance funds ?, and what are the legal implications of the perpetrators of crimes that have returned the state losses to PNPM aid funds?. The results of the research show that the proof of the real amount of loss for the state due to corruption is important in relation to criminal imposition (additional) payment of substitute money in the amount equal to that obtained / the result of criminal acts of corruption.Returning state losses by the defendant can be a reason for the judge to reduce the sentence imposed on the defendant concerned. With the return of the state's losses the defendant was deemed to have good intentions to correct errors.Refunds only reduce crime, but do not reduce the nature of the law, and sanctions against the return of state losses are emphasized on the return of replacement money, and confirmation of the imposition of criminal sanctions.